THE CORRELATION BETWEEN THE STUDENTS’ SIMPLE PAST TENSE MASTERY AND THEIR PARAGRAPH WRITING PERFORMANCE AT THE TENTH CLASS OF SMK MUHAMMADIYAH 1 METRO ACADEMIC YEAR 2011/2012 - Siti Komariyah (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2012)
Writing is a language skill that is used for indirect communication to convey a message or information to the readers. In writing a text, we can explore our ideas, feelings and thoughts which are arranged in words, sentences, and paragraph by using eyes, brain and hand. In writing a text, we must be able to use a good language and we also must be able to arrange good sentences grammatically in order the readers understand about the content of our writing. Besides that, if the students will make a sentences or paragraph, they must have knowledge about tenses. The objectives of the research are to find out the students’ simple past tense mastery and their paragraph writing performance and also to find out whether or not there is a correlation between the students’ simple past tense mastery and their paragraph writing performance. The subjects of this research are the tenth grade of SMK Muhammadiyah 1 Metro (class XTKJ1 and class XP). In this research, the writer used descriptive quantitative method because the final score of variable is number and the analysis is using statistic. The writer tried to analyze the current data about students’ simple past tense mastery and their performance in writing. In collecting data, the writer administered two kinds of test. They are simple past tense test and writing test. The simple past tense test are consists of 10 items of multiple choice and the writing test, the students choose one of topics from three topics. The result of this research shows that the students’ simple past tense mastery was middle. It can be seen from the average of simple past tense test is 69.2. The students’ performance in paragraph writing was middle. It can be seen from the average of paragraph writing performance test is 65.2. The conclusion above was from result of data analysis; it was found that paragraph writing performance affected by simple past tense mastery.